Molecular beams - Ramsey, Norman, 1915-; Oxford University Press (Oxford : Clarendon, 1956)
The author was joint Nobel Laureate in Physics in 1989. This book, first published in 1956, represents a contribution to the literature of atomic and molecular structure. As the title implies, the contents are limited to an account of beams of electrically neutral particles.
Includes bibliographical references and index.
Keywords: Molecular beams